Vietnam-the US relationship and effects on economic cooperation - Nguyen, Minh Trang; Tran, Phương Dung (International Journal of Scientific Research and Management (IJSRM), 2024)
The paper explores the dynamic relationship between the United States and Vietnam since the establishment of bilateral relations in 1995 until its milestone in 2023: comprehensive strategic partnership. Grounded in mutual respect and cooperation, their partnership has flourished across economic, political, security, and social spheres. Economically, the two countries have become each other's top trading partners, with bilateral trade turnover reaching $124 billion USD in 2023, a significant increase from $450 million USD in 1995. The United States has emerged as Vietnam's second-largest trading partner, underscoring the depth of economic integration. Additionally, the United States ranks 11th in terms of foreign direct investment (FDI) in Vietnam (2022), reflecting growing economic ties. Beyond economics, cooperation extends to political and diplomatic relations, defense and security, science and technology, education and training, environment and health, and humanitarian assistance/disaster relief. Vietnam, as a developing country in the globalization process, seeks diversified and substantive relationships for efficient and harmonized development.